Surgical treatment of ventral and ventrolateral intradural extramedullary tumors of craniovertebral and upper-cervical localization - Zozulya, Yuri P. (Annals of Cardiac Anaesthesia, 2010)
INTRODUCTION: Surgical treatment of extramedullary craniovertebral and upper-cervical tumors differs essentially, depending on the peculiarities of their localization. MATERIALS AND METHODS: In the Spinal department of the Institute of Neurosurgery during the period from 2000 to 2010 years, 96 patients with ventral and ventrolateral intradural extramedullary craniovertebral tumors and tumors of upper-cervical localization were examined and operated. The patients were distributed as follows: tumors of the craniovertebral localization – neoplasms spreading in rostral direction up to the boundary of the lower third of the clivus, and in caudal direction up to the upper edge body of the axis (C0 – C1): 12patients; tumors at the C1 – C2 level: 28 patients and at 1 – C2 – C3 level: 56 patients. The tumors were also divided as: ventral – 60 patients and ventrolateral – 36 patients. CONCLUSION: Therefore, the adequate choice of a surgical approach firstly depends on the localization of the tumor, its size and the extent to which it has spread. Far-lateral and posterolateral approaches in most cases are the most optimum and the least traumatic in cases of extramedullary ventrolateral tumors of craniovertebral and upper cervical localization. The extreme lateral approach is advisable in cases of large sized ventral craniovertebral tumors.